Numerical Study of Effect of Blade Twist Modifications on the Aerodynamic Performance of Wind Turbine - Beabpimai, Wiroj; Chitsomboon, Tawit (International Journal of Renewable Energy Development, 2019)
This paper aims to investigate aerodynamic performance of a wind turbine blade with twist modifications using computational fluid dynamics (CFD). The phenomenon of 3D stall-delay effect in relation to blade twist is the key feature to be investigated in order to improve efficiency of a wind turbine. The NREL (National Renewable Energy Laboratory) Phase VI wind turbine rotor was used for validation and as the baseline rotor. The baseline blade geometry was modified by increasing/decreasing the twist angles in the inboard, mid-board and outboard regions of the blade in the form of a symmetrical curve with maximum twist angle of 3°. The steady incompressible Reynolds-averaged Navier-Stokes (RANS) equations with the k-ω Shear Stress Transport (SST) turbulence closure model were used for the calculations at wind speeds ranging from 5-20 m/s. The computational results for the baseline Phase VI rotor were validated against experimental data and a good agreement was found. The computational results for the modified blades were compared against those of the baseline blade. It was found that increase of annual energy production of up to 5.1% could be achieved by this modification technique. ©2019. CBIORE-IJRED. All rights reserved